EFFECT OF RELATIONSHIP QUALITY TO BSI BRANCH PEMUDA JAKARTA CUSTOMER LOYALTY - Asyifa Putri Alifah; Husnul Khotimah Sylvia; Badrah Uyuni; Muhammad Adnan (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2022)
The high level of competition requires banking companies to pay attention to the importance of the elements of relationship quality (relationship quality) as an effort to retain existing customers. And This study aims to determine what factors affect relationship quality (quality of relationship) to loyalty customers at Bank Syariah Indonesia Jakarta Pemuda Branch Office. Study This study uses a quantitative approach and for this research sample is taken by using the slovin formula with a sample of 100 customers. Research data collection techniques were collected using observation techniques and questionnaires (questionnaire). Data analysis techniques in this study using Instrument Test (Validity & Reliability), Classical Assumption Test (Normality & Multicollinearity), Model Test (Simple Linear Regression, Coefficient Determination & Partial Correlation), Hypothesis Testing (t Test). Data processing in This research uses the SPSS (Statistical Package For Theft) software program Social Science) version 16.0 for windows. From the results of data processing Assumption Test Classical data is normal, from the results of the relationship quality t test (quality relationship) has a sig value of 0.00 < 0.05 which means that it has a significant significant to customer loyalty, from the results of the Coefficient of Determination Test The obtained R-Square value is 0.080 which means it has a strong relationship by 80% of customer loyalty while 20% is influenced by the variable other. The results of this study prove that relationship quality relationship) has a significant effect on customer loyalty at Islamic banks Indonesia Youth Branch Office.